A Review of Visible and Concealed Weapon Detection Techniques Using Machine Learning and Deep Learning - Sandhu, Simratjit kaur; Bhatia, Rekha (SN computer science, 2025)
The Gun violence facing the international society is an epidemic to which the world experts have been striving to find a solution to, since a long time. Gun violence endangers the fundamental human right to live. It affects all aspects of modern society. The availability and easy access to the weapons these days appears to be the most contributing factor to atrocities committed with them. Numerous researches suggest that the mere awareness of access to a weapon increases the possibility that a crime is most likely to occur. The most dangerous crimes have been committed in countries with loose laws on the possession and ownership of guns. Governments and security agencies around the world have been working tirelessly to come up with efficient mechanisms to counter the ever-increasing threat of guns. Advancements in computer vision technology appear to be the silver lining that can guide the efforts towards making the world a safer place. After numerous trials and errors over the years, the researchers have zeroed in on the automatic weapon detection in public as well as private spaces to be the best solution to combat the increasing incidents of gun violence. CCTV cameras have long been used as monitoring devices, but with technological advancements they can be transformed into intelligent alerting devices that can sound alarms even in the absence of a human operator, in case of an anomaly detection. Autonomous detection through CCTV surveillance has replaced walk-through systems, since automatic systems are more proactive, less invasive, and less obvious to perpetrators of crime. As far as detection is concerned, Faster R-CNN and YOLO algorithms seem to be the preferred choices. From the research, it has been demonstrated that the techniques of pre-processing, augmentation, use of realistic and synthetic datasets improve the performance of detection. To help researchers in the field of automatic weapon detection, an extensive review has been done with the aim of covering the developments that have been done in the said field along with future directions and challenges associated with it. This review covers various machine learning, deep learning algorithms used for weapon detection, as well as the various datasets and the multiple challenges associated with the field.